Realigning theory with evidence to understand the role of care coordination in mental health services research. (June 2023) - Hynes, Denise M; Thomas, Kathleen C
Current theoretical models intended to guide health services research and evaluation lack care coordination-its features and impacts. These aspects are critical for understanding the role of care coordination in healthcare use, quality, and outcomes. In this Focus article, we briefly review the well-known Andersen individual behavioral model (IBM) of healthcare use and the Donabedian health system and quality model (HSQM) together with recent practice-based evidence. We propose a new integrated theoretical model of healthcare and care coordination. The model can serve as a guide for future research to better understand the variation in care coordination services and delivery and its added value to improving mental health in different real-world settings.